1996
DOI: 10.1177/088307389601100608
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Diaminopyridine in Childhood Myasthenia: Double-Blind, Placebo-Controlled Trial

Abstract: Eleven patients with congenital and five with juvenile myasthenia gravis, aged 5 to 24 years, were given 3,4-diaminopyridine in a double-blind, placebo-controlled, crossover study. Clinical improvement was observed in 5 of 11 congenital myasthenia patients, and placebo effect, in 3 of 11. Juvenile myasthenia patients did not respond. Single-fiber electromyographic studies did not reveal any changes correlating with the clinical status of the patient. This study demonstrates the importance of double-blind and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…23 A favorable response to 3,4-DAP combined with pyridostigmine in unselected CMS patients was previously reported, 24 but another clinical trial of CMS patients with predominantly ocular symptoms found little response to 3,4-DAP. 25 In our experience, 3,4-DAP increases endurance and reduces lid ptosis, but external ocular muscles respond less than limb muscles and in some patients the medication becomes less effective with continued use. Patients with low-expressor or null mutations in each allele of the AChR ⑀ subunit can partially substitute the fetal ␥ for the ⑀ subunit.…”
Section: Management Of Different Types Of Cmss Endplate Achr Deficienmentioning
confidence: 81%
“…23 A favorable response to 3,4-DAP combined with pyridostigmine in unselected CMS patients was previously reported, 24 but another clinical trial of CMS patients with predominantly ocular symptoms found little response to 3,4-DAP. 25 In our experience, 3,4-DAP increases endurance and reduces lid ptosis, but external ocular muscles respond less than limb muscles and in some patients the medication becomes less effective with continued use. Patients with low-expressor or null mutations in each allele of the AChR ⑀ subunit can partially substitute the fetal ␥ for the ⑀ subunit.…”
Section: Management Of Different Types Of Cmss Endplate Achr Deficienmentioning
confidence: 81%
“…1-6 was combined with the terms: 7. treatment, 8. medication, 9. therapy, 10. controlled clinical trial, 11. randomized controlled trial, 12. clinical trial, 13. multicenter study, 14. meta-analysis, 15. cross-over studies, 16. thymectomy and 17. immunosuppression.…”
Section: Methodsmentioning
confidence: 99%
“…In a double‐blind, placebo‐controlled trial, the drug seemed effective in congenital (hereditary and non‐immune) myasthenia patients. Juvenile patients with MG did not respond [16] (class III evidence). The drug is not recommended in autoimmune MG, although it may prove useful in some forms of congenital myasthenia (level C recommendation).…”
Section: Myasthenia Gravis (Mg)mentioning
confidence: 99%
“…In a double‐blind, placebo‐controlled trial the drug seemed effective in congenital (hereditary and non‐immune) myasthenia patients. Juvenile MG patients did not respond [13] (class III evidence). The drug is not recommended in autoimmune MG although it may prove useful in some forms of congenital myasthenia (level C recommendation).…”
Section: Myasthenia Gravismentioning
confidence: 99%